Nahdlatul Ulama and the Struggle for Power within Islam and Politics in Indonesia - Bush, Robin (Book collections on Project MUSE., 2009)
This is the most comprehensive account of the internal dynamics of the young intellectual generation of NU advocating for pluralism and democracy within Islam in Indonesia, during Gus Dur's leadership of PBNU. Because of the author's unique vantage point, her sometimes sharp criticism of this movement and its internal dynamics is extremely useful to those who continue to advocate for reform, within NU and in Indonesia generally. - Ahman Suaedy, Executive Director, Wahid Institute, Jakarta ...